1975
DOI: 10.1139/m75-036
|View full text |Cite
|
Sign up to set email alerts
|

Simplified procedures for releasing and concentrating microorganisms from soil for transmission electron microscopy viewing as thin-sectioned and frozen-etched preparations

Abstract: A simplified procedure is presented for releasing and concentrating indigenous microbial cells from soil for viewing by transmission electron microscopy as thin sections or replicas of frozen-etched preparations. This procedure is compared with two others reported earlier, and their relative merits are discussed as concerns the choice of procedure for the cellular information desired from the soil. Freeze-etching showed that the cell types and size distributions for cells which have been released and concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This is corroborated by the fmding that plate counts and microscopic counts gave about the same yield (Faegri et al 1977~ Holben et al 1988. Balkwill et al (1975) observed little difference when studying the size distribution of soil bacteria using electron microscopy before and after separation by a centrifugation procedure similar to the one described here. The bacterial fractions may be stored as pellets after the last centrifugation, either at -20°C or in the refrigerator with isopropanol added (Rake 1972).…”
Section: Fractionation Efficiencymentioning
confidence: 69%
“…This is corroborated by the fmding that plate counts and microscopic counts gave about the same yield (Faegri et al 1977~ Holben et al 1988. Balkwill et al (1975) observed little difference when studying the size distribution of soil bacteria using electron microscopy before and after separation by a centrifugation procedure similar to the one described here. The bacterial fractions may be stored as pellets after the last centrifugation, either at -20°C or in the refrigerator with isopropanol added (Rake 1972).…”
Section: Fractionation Efficiencymentioning
confidence: 69%
“…This biovolume of bacteria was smaller than that mentioned above, presumably due to the fact that the cocci in the 0.5 .urn diameter class accounted for 60-70% of the total number of bacteria. As BALKWILL et al (4) mentioned, the average diameter of bacteria in soil was less than 0.5 .urn. Therefore the authors also assume that the average biovolume of bacteria in soil was 0.2-0.3 .um3.…”
Section: Microbial Biomass 1) Bacterial Biomassmentioning
confidence: 93%
“…BALKWILL et 01. (4) showed that a sizeable portion (ranging from 27 to 83%, depending on conditions and soils) of the soil microbial cells are small dwarf cells, 0.3 pm in diameter based on electron microscopic observations of soil. The results of Balkwill et 01. agree with those of the authors who showed that the bacterial numbers were about ten times as high as those of the former results, and that the number of small cocci (diameter =0.5 pm) accounted for 60-70% of the total number of cocci.…”
Section: Bacterial Countsmentioning
confidence: 99%
“…Soil microorganisms can be dislodged from soil debris and then concentrated so that they can be viewed by transmission electron microscopy as either thinsectioned or fi'ozen-etched preparations (Bae, Cota-Robles and Casida, 1972;Bae and Casida, 1973 ;Balkwill and Casida, 1973 ;Balkwill, Labeda and Casida, 1975;Labeda, Balkwill and Casida, 1975). Bae and Casida (1973) accomplished this with an exhaustive centrifugal washing procedure that involved a combination of hand shaking, sonication at 4 different energy levels, 32 low-speed centrifugations at 4 different centrifugal forces, and a final Ludox density gradient centrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure efficiently concentrated the soil cells and removed gritty soil debris so that the preparations, as viewed by transmission electron microscopy, contained only small amounts of soil debris. Balkwill et al (1975) markedly shortened and simplified this approach while retaining the high cell-recovery yields. In their procedure, designated as method B, the microbial cells in a soil sample were released and separated from the soil materials by sequentially applying two blendings and two sonications, each in a fresh portion of pyrophosphate solution.…”
Section: Introductionmentioning
confidence: 99%